2017
DOI: 10.3389/fpls.2017.01650
|View full text |Cite
|
Sign up to set email alerts
|

The Plant Immunity Regulating F-Box Protein CPR1 Supports Plastid Function in Absence of Pathogens

Abstract: The redox imbalanced 6 mutant (rimb6) of Arabidopsis thaliana was isolated in a genetic screening approach for mutants with defects in chloroplast-to-nucleus redox signaling. It has an atypically low activation status of the 2-Cys peroxiredoxin-A promoter in the seedling stage. rimb6 shows wildtype-like germination, seedling development and greening, but slower growth and reduced biomass in the rosette stage. Mapping of the casual mutation revealed that rimb6 carries a single nucleotide polymorphism in the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 93 publications
(172 reference statements)
0
12
0
Order By: Relevance
“…Other resistant candidate genes include the zinc finger (Gupta et al, 2012 ) and plant PDR ABC transporter (Nuruzzaman et al, 2014 ; Sekhwal et al, 2015 ), as shown in Table 4 . The protein containing the F-box domain, Thecc1EG028293t1, might be associated with accumulation of phytohormones in response to pathogen infection (Liu and Xue, 2011 ; Piisil et al, 2015 ; Gonzalez et al, 2017 ; Hedtmann et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other resistant candidate genes include the zinc finger (Gupta et al, 2012 ) and plant PDR ABC transporter (Nuruzzaman et al, 2014 ; Sekhwal et al, 2015 ), as shown in Table 4 . The protein containing the F-box domain, Thecc1EG028293t1, might be associated with accumulation of phytohormones in response to pathogen infection (Liu and Xue, 2011 ; Piisil et al, 2015 ; Gonzalez et al, 2017 ; Hedtmann et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Papain-like cysteine proteases (PLCPs) control key processes and are a central hub in plant immunity (Richau et al 2012;Misas-Villamil et al 2016). F-Box Protein CPR1 is well-known for its effect on plastid function in the absence of pathogens (Hedtmann et al 2017). Secondary metabolism plant glycosyltransferases (UGTs) are a large family of plant genes known for their putative function during plant-pathogen interactions (Langlois-Meurinne et al 2005).…”
Section: Annotation Of Disease Resistance Genesmentioning
confidence: 99%
“…Spreading of the priming effect can be mediated by the plasma membrane ROS generating complex RbohD/F (Carmody et al, ) and stimulates biosynthesis of SA, JA, and NO (Gruner, Griebel, Navarova, Attaran, & Zeier, ; Hung & Kao, ; Kalbina & Strid, ; Scott et al, ; Vlot et al, ; Xu et al, ). These secondary signals stabilize ROS‐regulated signalling (Bi, Kenton, Mur, Darby, & Draper, ; Gruner et al, ; Hedtmann et al, ; Hossain et al, ; Kacperska, ). SA treatments can directly prime, for example, maize, cucumber ( Cucumis sativus ), and rice for higher cold tolerance (Kang & Saltveit, ) and induce expression of glutathione reductase and guaiacol peroxidase.…”
Section: Combining the Exemplary Studies Into A Hypothesis On The Promentioning
confidence: 99%